Oh, as for the Health Insurance…it’s good, but…: rural elders in Agate, Ghana, discuss the National Healthcare Insurance Scheme - Eileen Smith-Cavros; Joyce Avotri-Wuaku; Albert Wuaku; Amal Bhullar (Qualitative Research in Medicine & Healthcare)
This paper investigates the Ghanaian National Healthcare Insurance Scheme (NHIS) through interviews with 28 elders over 50 years old with pre-existing illnesses in Agate, a rural village in Ghana. Our goals were to obtain snapshot views of the lives, in relation to health, wellness, and NHIS, of participants. Elders possessed reasonable information about NHIS. For most enrollees, NHIS provided peace of mind against financially-related health challenges, however, inability to afford non-covered medicines sometimes interfered with treatment. Most interviewees, insured or not, reported continuing chronic health problems. Based on qualitative data, we describe possibilities to improve elder experiences including: transportation to medical care, increased drug coverage, and faith-based health partnerships.